Intra- and Inter-Regional Priming of Ipsilateral Human Primary Motor Cortex With Continuous Theta Burst Stimulation Does Not Induce Consistent Neuroplastic Effects - Do, Michael; Kirkovski, Melissa; Davies, Charlotte B.; Bekkali, Soukayna; Byrne, Linda K.; Enticott, Peter G. (Frontiers in Human Neuroscience, 2018)
Human responses to non-invasive brain stimulation (NIBS) techniques can be highly variable. Recently, priming protocols involving a conditioning round of NIBS applied to a target brain region prior to the application of a test protocol have shown promise in inducing more reliable effects. We investigated whether intra- or inter-regional priming of the left primary motor cortex (M1) using continuous theta burst stimulation (cTBS) can induce consistent, and reliable modulation of corticospinal excitability. Twenty healthy adults (6 males) underwent four cTBS protocols. For intra-regional priming, cTBS was applied twice to the left M1 (M1-M1). For inter-regional M1 priming, cTBS was applied to the ipsilateral (left) dorsal premotor cortex (dPMC-M1), and ipsilateral (left) dorsolateral prefrontal cortex (DLPFC-M1). In the control condition, sham stimulation was applied to left M1, followed by active cTBS also applied to the left M1 (sham-M1). Each round of cTBS was separated by 10 mins. Neuroplastic responses were indexed using motor evoked potentials (MEPs) elicited from the left M1 hand region, and measured from the contralateral first dorsal interosseous (right hand). MEP measurements were taken before the first round of cTBS priming, then immediately, 10, 20, and 30min after the second test round of cTBS. The primary two-way repeated measures ANOVA revealed no significant differences in MEP responses across each condition (no main effects or interaction). Intra- and inter-regional priming of the left M1 using cTBS does not induce consistent neuroplastic effects. Further work is required to identify factors which contribute to such variability in human responses to NIBS.